Somatostatin receptors over-expression in castration resistant prostate cancer detected by PET/CT: preliminary report of in six patients - Savelli, Giordano; Muni, Alfredo; Falchi, Roberta; Zaniboni, Alberto; Barbieri, Roberto; Valmadre, Giuseppe; Minari, Chiara; Casi, Camilla; Rossini, Pierluigi (Annals of Translational Medicine, 2015)
Prostate cancer (PC) is usually characterized by an excellent prognosis, largely due to little biological aggressiveness and the power of hormonal deprivation therapy. In spite of these favorable characteristics, however, a significant quota of patients does not respond to androgen deprivation therapy (ADT) and develop a progressive disease. Castration-resistant prostate cancer (CRPC) is defined by disease progression in spite of ADT. This progression may show any combination of a rise in serum prostate-specific antigen (PSA), clinical and radiological progression of pre-existing disease, and appearance of new metastases. This event is a striking change in the clinical scenario, since the power of treatment for CRPC patients with distant metastases is very limited. Somatostatin is a hormone produced by neuroendocrine cells. Its distant effects are mediated by the binding to five specific receptors, which are the most striking parameter for neuroendocrine. Various synthetic somatostatin agonists able to bind to the receptors have been synthesized during the past two decades for diagnostic and therapeutic purposes. Octreotide, the most popular of these, is widely used to treat patients affected by neuroendocrine tumors. A number of researches carried out in the past evaluated the possible neuroendocrine differentiation (NED) of PC cells in the castration resistant phase. If proved, the presence of a specific class of receptor on cell’s surfaces should give a potentially biological target to be used for therapy. However, these studies led to contradictory results. Aim of our phase III diagnostic trial was to study “in vivo” the over-expression of somatostatin receptors (SSTRs) in CRPC patients by PET/CT after the administration of the somatostatin analog [68Ga-DOTANOC,1-Nal(3)]-octreotide labeled with 68Ga. Every area of increased uptake corresponding to a metastasis detected with other methods was considered as SSTRs expressing. False positivity to SSTRs expression was considered those localizations with a suspicious uptake not confirmed by other radiologic procedures. On the other hand, metastatic lesions lacking the radiopharmaceutical’s uptake were considered not SSTRs expressing metastases. The preliminary results in 6 of the 67 patients scheduled by our phase III trial showed metastases with a variable SSTRs expression in 2 patients.